2017
DOI: 10.1128/jvi.01677-16
|View full text |Cite
|
Sign up to set email alerts
|

The Long and Complicated Relationship between Epstein-Barr Virus and Epithelial Cells

Abstract: The roles of epithelial cells in infection and persistence of the EpsteinBarr virus (EBV) have long been difficult to resolve. However, recent developments have reinforced the conclusion that these cells are a major site of virus replication and raised the possibility that, like papillomaviruses, EBV has evolved to take advantage of epithelial differentiation to ensure survival, persistence, and spread.KEYWORDS Epstein-Barr virus, epithelial cells, tropism E pstein-Barr virus (EBV) is well known as a human lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
60
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 25 publications
(24 reference statements)
0
60
0
2
Order By: Relevance
“…EBV infection is generally found in B-lymphocytes, but the virus is also thought to infect polarized epithelium through the formation of direct adhesions between the B cells and the basolateral surface of epithelial cells [110,111], utilizing the endocytic recycling pathways of both donor and recipient cell to facilitate direct cell-cell transmission of the virus [112,113]. It has also been suggested that the virus exploits the endosomal machinery to cross the epithelial cells of the oral mucosa, without initiating an infection, to directly infect the B lymphocyes in the underlying dermis [112,114].…”
Section: Tumor-associated Herpesvirusesmentioning
confidence: 99%
“…EBV infection is generally found in B-lymphocytes, but the virus is also thought to infect polarized epithelium through the formation of direct adhesions between the B cells and the basolateral surface of epithelial cells [110,111], utilizing the endocytic recycling pathways of both donor and recipient cell to facilitate direct cell-cell transmission of the virus [112,113]. It has also been suggested that the virus exploits the endosomal machinery to cross the epithelial cells of the oral mucosa, without initiating an infection, to directly infect the B lymphocyes in the underlying dermis [112,114].…”
Section: Tumor-associated Herpesvirusesmentioning
confidence: 99%
“…In particular, the time and site of EBV involvement during tumor development is still circumstantial and controversial. For example, it remains unknown whether NPC tumor cells are infected by cell‐free EBV or by transferred infection from EBV‐positive memory B cells via the cell‐cell contact manner …”
Section: Introductionmentioning
confidence: 99%
“…For example, it remains unknown whether NPC tumor cells are infected by cell-free EBV or by transferred infection from EBV-positive memory B cells via the cell-cell contact manner. 8 Chromogenic in situ hybridization (ISH) of EBER has been reported to be the gold standard for detection of EBV-infected cells. [9][10][11] The reliable detection is somewhat hampered by the lack of robustness and sensitivity of this technique.…”
Section: Introductionmentioning
confidence: 99%
“…The EBV lytic stage is essentially required for horizontal transmission and lifelong persistence, and has a poorly understood role in the development of viral malignancies (7). In addition to epithelial cells in the oropharynx (8), resting peripheral blood and tonsil memory B cells are thought to serve as reservoirs for latent EBV (2, 9), while mature B cell trafficking through the GC and terminal differentiation into CD38+ plasma cells can trigger EBV reactivation (10). In vitro, cross-linking of surface immunoglobulins (Ig) on freshly isolated EBV-positive B cells (11) or latently infected BL cells (12) functionally mimics antigen interactions and stimulates virus reactivation.…”
Section: Introductionmentioning
confidence: 99%